Analysis of risk factors associated with cervical HPV infection and their effects on female sexual function and anxiety: a multicenter cross-sectional study based on Chinese women - Wang, Haoye; Nie, Keyi; Liu, Zixuan; Zhao, Yumeng; Ha, Yingxin; Zhang, Huanyan (Frontiers in Oncology, 2024)
IntroductionThis research aimed to explore the determinants of cervical HPV infection and evaluate how cervical cancer screening outcomes influence sexual functioning and anxiety among women across three provinces in China.MethodsStudy participants were categorized into HPV-positive or HPV-negative groups, after which they completed the General Characteristics Questionnaire and the SAS Anxiety Scale. The HPV-positive cohort was further divided into four subgroups: Subgroup 1 consisted of individuals with HPV types 16 or 18 but no cytological abnormalities. Subgroup 2 included those with cytological abnormalities and infections with HPV types 16 or 18. Subgroup 3 included participants infected with high-risk HPV types other than 16 and 18, who did not show cytological abnormalities, while Subgroup 4 encompassed individuals with both cytological abnormalities and infections with high-risk HPV types other than 16 and 18. All participants were assessed using the Female Sexual Function Index Scale (FSFI), which measures sexual function across these subgroups.ResultsA total of 531 questionnaires were analyzed. Logistic regression identified several risk factors for HPV infection, including manual labor, service occupations, other occupations, low- and middle-income groups, and cervical columnar epithelial ectasia, as well as an increase in the number of previous sexual partners. Conversely, protective factors included condom use during sexual activity and mutual genital hygiene prior to intercourse. The incidence of lower genital tract infections was significantly higher in the HPV-positive group compared to the HPV-negative group, with rates of chlamydia (13.3% versus 4.6%, P<0.001), gonococcal infections (5.2% versus 0.4%, P<0.001), and mycobacterial diseases (38.9% versus 23.4%, P<0.001). Additionally, anxiety levels were significantly higher in the HPVpositive group compared to the HPV-negative group (p<0.005). Anxiety levels and cytological outcomes were significantly correlated across the four HPV-positive subgroups (p<0.05), with type 16/18 infections being associated with notably lower FSFI scores compared to other high-risk HPV types (p<0.05).ConclusionsThe findings suggest that infections with HPV type 16/18, especially when accompanied by abnormal cytological findings,significantly elevate anxiety and distress in women and are associated with reduced FSFI scores. These results highlight the complex impact of HPV infection on women’s sexual health and psychological well-being with HPV type 16/.